Participation and Achievements of Modern Pentathlon Athletes at the 2025 Madiun Mayor's Cup Provincial Championship - I Made Dwi Sastra Wargama; Bagus Dwi Cahyono; Andy Widhiya Bayu Utomo (CV. SAMODRA INSAN PENA, 2025)
Modern pentathlon is a multidisciplinary sport that combines physical endurance, technical skills, and psychological readiness within a single competitive setting. At the regional level, provincial championships play a strategic role in evaluating athlete development, identifying participation patterns, and assessing the effectiveness of coaching systems. This study aimed to describe athlete participation and performance at the 2025 Indonesian Modern Pentathlon Provincial Championship (Madiun Mayor’s Cup) using official competition data. This study employed a quantitative descriptive design with a retrospective approach. Secondary data were obtained from the official championship results book, covering all registered athletes who participated in the competition. The subjects included male and female athletes from U-9 to senior age categories, competing in biathle, triathle, and laser run events across individual, relay, and mixed relay formats. Data analysis was conducted descriptively using frequency and percentage calculations to examine participation by age group, gender, event, and region of origin, as well as performance indicators including athlete rankings, podium distribution, and regional dominance. The results showed that athlete participation was highest in the U-9 to U-15 age groups, indicating a strong foundation of early-stage development in modern pentathlon. However, a noticeable decline in participation occurred at the junior and senior levels, suggesting challenges in sustaining athlete progression to higher competitive stages. Performance analysis revealed that podium achievements were distributed across several regions, with Madiun City, Surabaya City, Pasuruan Regency, Kediri City, and Malang Regency demonstrating the most consistent dominance. Differences in performance between events and age groups reflected variations in training quality, competition experience, and athlete readiness. In conclusion, the 2025 Madiun Mayor’s Cup Provincial Championship functioned not only as a competitive event but also as an effective evaluation platform for regional modern pentathlon development. The findings emphasize the importance of data-driven coaching strategies and sustainable long-term athlete development pathways to enhance competitive performance